Longitudinal effects of exercise according to the World Health Organization guidelines on cognitive function in middle-aged and older adults - Dasom Kim; Young Ko; Aeri Jung (Frontiers Media S.A., 2022)
PurposeTo investigate the longitudinal effects of adequate exercise, defined as an exercise duration of ≥150 min/week by the World Health Organization (WHO), on cognitive function in middle-aged adults.MethodsThis study was a longitudinal panel analysis using secondary data obtained from the Korean Longitudinal Study of Aging (KLoSA) database, with 4,825 participants registered and comprising five rounds of survey data in 2-year intervals from 2010 to 2018. The participants were divided into the adequate exercise (≥150 min/week), deficient exercise (<150 min/week), and no exercise groups according to the WHO definition, and their cognitive decline over the 8-year period was analyzed. Further, we investigated the longitudinal effects of exercise using a fixed effects model with cognitive function as the dependent variable.ResultsIn the dementia group, both deficient (<150 min/week) and adequate (≥150 min/week) exercises had statistically significantly positive effects on cognitive function. However, the coefficient size was not significantly larger in the adequate exercise group than in the deficient exercise group. In the participants with mild cognitive impairment (MCI), an adequate exercise level had significantly positive effects on cognitive function, while a deficient exercise level did not. In the participants with normal cognition, an adequate exercise level was not significantly associated with changes in cognitive function.ConclusionContinuous exercise can have a positive influence on cognitive function scores in middle-aged and older adults with MCI or dementia, but the findings cannot substantiate that adequate exercise (≥150 min/week) is more effective compared to deficient exercise (<150 min/week).